Trust-Based Trade Mechanism and Its Impact on Rural Economic Development: A Case Study of Farmers and Middlemen in Purwodadi Village, Central Kalimantan - hidayat, Aly; Akbar, Wahyu; Safitri, Novi Angga; Widagdo, Haidi Hajar (Yayasan Riset dan Pengembangan Intelektual, 2025)
This research aims to explore the trading practices between farmers and middlemen in Purwodadi Village, Central Kalimantan, focusing on the trade of key limes and kecombrang (torch ginger), while analyzing the transaction mechanisms, evaluating them from the perspective of Islamic economics, and determining their socio-economic impacts. Using a qualitative descriptive approach, the study was conducted in Purwodadi Village, with middlemen and farmers involved in the trade as the research subjects and the trading activity itself as the research object. Data were collected through non-participant observation, semi-structured interviews, and documentation. The findings reveal that the trading mechanism is based on trust and strong social relationships, with farmers choosing to sell their harvest to middlemen for market certainty and ease of distribution, while middlemen secure a stable supply of goods. From the perspective of Maqashid Sharia (the objectives of Islamic law), this system reflects principles of justice and benefit, as transactions are conducted fairly and mutually beneficially. This research contributes to understanding trading practices through the lens of Maqashid Sharia, which has not been extensively studied in local trade contexts, affirming the crucial role of social relationships and trust in sustaining traditional trading systems. Additionally, it provides insights into how principles of justice and benefit are applied in rural economic practices, offering a new perspective in Islamic economic studies, particularly in assessing trust-based transactions in the agricultural sector.